Moving beyond mere exams to build up character - Abd Razak, Dzulkifli (2005)
The suggestion made by the Ministry of Higher Education to include cocurricular contribution as part of the coming university intake appears to have received support all around. Many reasoned that this is a timely move given that Malaysia needs a new generation of "education" citizens as awe move closer to 2020. For too long, Malaysia has been measuring success based on a rigidly examoriented system. Though no doubt there have been a number of achievements that we can be proud of, the question is at what expense? For instance, how about our performance in sports, our social etiquette, moral and ethical standards and other sociocultural indicators? Of late, these have been hogging the headlines almost daily, raising grave concern across the nation.